Black aluminum oxide porous ceramic material for vacuum chuck and preparation method of black aluminum oxide porous ceramic material
By adjusting the ratio of iron oxide, chromium trioxide, cobalt trioxide and nickel oxide, and combining other additives and materials, a uniform color and high performance black alumina porous ceramic material was prepared, which solved the problem of insufficient color purity of existing materials and difficult industrial production, and realized the preparation of vacuum suction cup materials suitable for the semiconductor industry.
Patent Information
- Application Number
- CN202411933485.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The color purity of existing black alumina porous ceramic materials is insufficient, the color purity of the inside and outside is inconsistent, and the preparation process is complicated, making it difficult to achieve industrial production.
Iron oxide, chromium trioxide, cobalt trioxide and nickel oxide are used as colorants, and by adjusting their ratio, combining additives such as polyacrylic acid, N-hydroxymethylacrylamide and N,N’-methylenebisacrylamide, and using materials such as white corundum and pore-forming agents, and using ball milling, centrifugal stirring and sintering to prepare a porous black alumina material with uniform color.
The prepared black alumina porous ceramic material has high compressive strength, high porosity, high bending strength, uniform color, simplifies the preparation process, facilitates industrial production, and is suitable for vacuum suction cup materials in the semiconductor industry.
Smart Images

Figure CN119899020A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alumina ceramics, and in particular to a black alumina porous ceramic material for a vacuum chuck and a preparation method thereof. Background Art
[0002] With the development of domestic science and technology, various electronic information components are gradually moving towards refinement and lightweight, and the demand for more thin-film products is also increasing. However, the process of transporting such materials cannot be separated from vacuum suction cups. Traditional vacuum suction cups are mostly made of metal materials by surface punching. This type of vacuum suction cup has a larger aperture and generates greater suction. When processing small-sized workpieces, it is easy to cause the workpiece to deform, and in severe cases, it is more likely to cause damage. Using ceramic vacuum suction cups, evenly distributed openings with an aperture of <100μm can be prepared. This new type of vacuum suction cup is conducive to accelerating the independent development of my country's semiconductor equipment.
[0003] Furthermore, for high-precision semiconductor components, especially photosensitive semiconductor components, they are extremely sensitive to ambient light during production and handling. Any unexpected light exposure may cause irreversible damage to the performance of photosensitive semiconductor components, thereby affecting the quality and reliability of the entire product. In this context, black alumina porous ceramics stand out with their excellent light shielding ability and become an ideal material for handling such sensitive components. Black alumina porous ceramics can effectively block ambient light and ensure that photosensitive semiconductor components are protected from light interference during processing, thereby protecting their photoelectric properties from damage. Especially in the production process of ultraviolet-sensitive semiconductor devices, the handling arm made of black alumina porous ceramics can effectively isolate ultraviolet radiation and prevent the performance of the device from degrading due to photoinduced effects, further improving the stability and reliability of the production process. However, the preparation process of the black alumina porous ceramics prepared in patent number CN117585990A is relatively complicated, and the color cannot be pure black, and the colors inside and outside are inconsistent, which greatly reduces the ability to effectively block ambient light, and industrial production is difficult. Summary of the invention
[0004] In order to solve the technical problems mentioned in the above background technology such as insufficient color purity, inconsistent internal and external colors, and difficulty in industrial production, the present invention provides a black alumina porous ceramic material for a vacuum suction cup and a preparation method thereof. The prepared porous ceramic has uniform color, high compressive strength, high apparent porosity, and high flexural strength, and the material preparation process is simple, which is convenient for industrial production.
[0005] The specific technical solution of the present invention is: a method for preparing a black alumina porous ceramic material for a vacuum chuck, comprising the following steps: 1) After mixing 4-5 parts of aluminum oxide powder, 10-11 parts of silicon dioxide powder, 7-8 parts of colorant and 20-25 parts of water by weight, add 0.5-1 parts of polyacrylic acid, 6-8 parts of N-hydroxymethyl acrylamide and N,N'-methylenebisacrylamide, and ball mill for 30-60 minutes; 2) Add 35-40 parts of white corundum coarse powder, 30-35 parts of pore-forming agent and 35-38 parts of suspending agent and centrifuge for 2-3 minutes, repeat 3-5 times; 3) Add 1-1.5 parts of ammonium persulfate and stir evenly, pour into a mold, and let stand at 60-65°C for 30-45 minutes; 4) After demoulding and drying, degreasing and sintering are performed to obtain a black alumina porous ceramic material for a vacuum chuck.
[0006] The invention uses iron oxide, chromium trioxide, cobalt trioxide and nickelous oxide as colorants, and the research team has conducted a large number of creative experiments to obtain the result that when the proportion of each component of the colorant is adjusted to iron oxide micropowder: chromium trioxide: cobalt trioxide: nickelous oxide = (2.8-3.2): (1.8-2.2): (1.3-1.5): (0.4-0.6), the aluminum oxide can present a uniform black color inside and outside after sintering, and the silicon dioxide micropowder with a smaller particle size is self-evaluated as a sintering aid, which is easier to generate a liquid phase on the surface of the white corundum skeleton; polyacrylic acid is used as a dispersant to disperse the aluminum oxide micropowder, the silicon dioxide micropowder and the colorant to form a uniform porous ceramic material, and N-hydroxymethyl acrylamide is used as an organic monomer, and N, N'-methylenebisacrylamide is used as a cross-linking agent, and injection molding is performed through an aqueous gel injection molding system, so that the use range of the material is expanded to the manufacture of parts with complex shapes and high precision requirements.
[0007] Furthermore, in step 1), the colorant is iron oxide powder, chromium trioxide, cobalt trioxide and nickelous oxide in a weight ratio of (2.8-3.2):(1.8-2.2):(1.3-1.5):(0.4-0.6).
[0008] Furthermore, in step 1), the particle size of the alumina powder is: 10 =0.3~0.35μm; D 50 =0.5~0.55μm; D 90 =3~3.1μm.
[0009] Furthermore, in step 1), the particle size of the silicon dioxide powder is: 10 =0.8~0.85μm; D 50 =1~1.05μm; D 90 =5~5.2μm.
[0010] Furthermore, in step 2), the white corundum coarse powder is fused white corundum, and the particle size is: 10 =10~11μm; D 50 =15~16μm; D 90 =25~26μm.
[0011] Further, in step 2), the pore-forming agent is one or more of polymethyl methacrylate, spherical graphite, and industrial starch, and the particle size is: D 10 =30~40μm; D 50 =45~55μm; D 90 =55~70μm, the pore-forming agent will burn and be eliminated in the form of gas during the degreasing process, leaving pores in situ. This method combines the sintering method and the template method to obtain porous ceramics with high apparent porosity.
[0012] Furthermore, in step 2), the suspending agent is one or more of polyvinyl alcohol and polyethylene oxide aqueous solutions with a concentration of 5 to 6 wt%. The use of the suspending agent can avoid the rapid sedimentation of the white corundum coarse powder.
[0013] Preferably, centrifugal stirring uses an industrial-grade rotation-revolution centrifugal mixer to quickly mix all the slurries. This method can degas the slurry while mixing, and can significantly improve the dispersibility of high-viscosity slurries, and further prevent the sedimentation of white corundum when the slurry solidifies.
[0014] Furthermore, in step 4), the drying process is: drying at 40-45° C. and relative humidity of 80-85% for 24-30 hours, drying at 60-65° C. and relative humidity of 40-45% for 24-30 hours, and finally drying at 80-85° C. and relative humidity of 20-25% for 24-30 hours.
[0015] Furthermore, in step 4), the temperature of debinding and sintering is 1400-1450° C., and the time of debinding and sintering is 2-3 hours.
[0016] Furthermore, a black alumina porous ceramic material for a vacuum chuck is prepared according to the method for preparing the black alumina porous ceramic material for a vacuum chuck.
[0017] Compared with the prior art, the beneficial effects of the present invention are: 1) The porosity of the alumina porous ceramic prepared by the present invention reaches 30-40%, the size of the open pores is evenly distributed, and the bending strength of the material is ≥100Mpa, which is significantly improved compared with the performance of traditional alumina porous ceramics and is suitable for alumina porous ceramic vacuum chucks in the semiconductor industry.
[0018] 2) The selection of colorant types and proportions can produce black alumina porous ceramics with uniform color inside and outside, broadening the application field of the material.
[0019] 3) Rough processing of ceramic green bodies can reduce the cost of finishing after sintering, streamline the process flow, facilitate industrial production, improve production safety, and at the same time reduce production costs and environmental pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the SEM electron microscope morphology of the porous ceramic prepared in Example 1. DETAILED DESCRIPTION
[0021] The present invention will be further described below in conjunction with the embodiments.
[0022] Unless otherwise specified, the raw materials used in the present invention can be purchased from the market or are commonly used in the art. Unless otherwise specified, the methods in the following embodiments are all conventional methods in the art.
[0023] Example 1 A black alumina porous ceramic material for a vacuum suction cup, and a preparation method thereof is as follows: 1) Preparation of slurry By weight, 42 parts of particle size D 10 =0.3μm, D 50 =0.5μm, D 90 = 3μm alumina powder, 11 parts particle size D 10 =0.8μm, D 50 =1μm, D 90 =5μm silicon dioxide powder, 3 parts of iron oxide powder, 2 parts of chromium trioxide, 1.5 parts of cobalt trioxide, 0.5 parts of nickelous oxide are mixed with 24 parts of deionized water, and then 1.5 parts of polyacrylic acid, 7 parts of N-hydroxymethyl acrylamide, and 0.5 parts of N, N'-methylenebisacrylamide are added, and ball milling is carried out for 60 minutes until the bulk material is uniform, and then 38 parts of coarse white corundum powder, 30 parts of polymethyl methacrylate microspheres, and 36 parts of polyvinyl alcohol aqueous solution with a mass concentration of 5% are added, and the mixture is poured into a rotation-revolution mixer and mixed at 2100rpm for 2 minutes. Repeat three times to obtain a uniformly mixed porous ceramic slurry.
[0024] 2) Injection Molding: Add 1 part of ammonium persulfate to the uniformly mixed porous ceramic slurry obtained in step 1), pour into a mold, and place in a water bath at 60° C. for 30 minutes to wait for molding.
[0025] 3) Material post-processing The formed ceramic processing material prepared in step 2) is dried in a constant temperature and humidity chamber at 25°C and 80% relative humidity for 12 hours, at 40°C and 60% relative humidity for 12 hours, and at 80°C and 20% relative humidity for 24 hours; degreasing and sintering are performed in an atmospheric atmosphere sintering furnace with a maximum sintering temperature of 1350°C and a holding time of 2 hours to obtain a porous ceramic material.
[0026] 4) Performance testing The density, flexural strength and apparent porosity of the porous ceramic material prepared in step 3) are tested, and the color of the prepared porous ceramic material is recorded, wherein the porosity is tested in accordance with GB / T25995-2010; the flexural strength is tested in accordance with GBT_6569-2006.
[0027] Figure 1 It clearly presents a skeleton morphology composed of white corundum, and its surface has obvious traces of alumina active matrix and silicon dioxide liquid phase coverage. The white corundum is interconnected to form a dense skeleton structure, which greatly enhances the mechanical strength of the material. Most of the pores are uniformly distributed and have obvious layered structures.
[0028] From the XRD test, it can be seen that the colorant, alumina and sintering aid react with each other to produce various spinel compounds, such as Cr 1.6 NiAl 0.4 O4, Cr 1.7 Fe 0.3 O3. When iron oxide, chromium trioxide, cobalt trioxide, and nickel oxide fully react with each other, black will be generated. If one of the colorants is too much, it will lead to incomplete reaction, resulting in color deviation. For example, in Comparative Examples 1 and 2, if chromium trioxide is too much, it will appear green, and if iron oxide is too much, it will appear red. Only when it appears black can it show a beneficial effect when transporting semiconductor parts.
[0029] Comparative Example 1 The difference between this comparative example and Example 1 is that in this comparative example, 2 parts of the colorant iron oxide powder and 3 parts of the colorant chromium trioxide are added in step 1), that is, the ratio of the colorant is changed, and the rest of the process is the same as that of Example 1, and the specific steps are as follows: 1) Preparation of slurry By weight, 42 parts of particle size D 10 =0.3μm, D 50 =0.5μm, D 90 = 3μm alumina powder, 11 parts particle size D 10 =0.8μm, D 50 =1μm, D 90=5μm silicon dioxide powder, 2 parts of iron oxide powder, 3 parts of chromium trioxide, 1.5 parts of cobalt trioxide, 0.5 parts of nickelous oxide are mixed with 24 parts of deionized water, and then 1.5 parts of polyacrylic acid, 7 parts of N-hydroxymethyl acrylamide, and 0.5 parts of N, N'-methylenebisacrylamide are added, and ball milling is carried out for 60 minutes until the bulk material is uniform, and then 38 parts of coarse white corundum powder, 30 parts of polymethyl methacrylate microspheres, and 36 parts of polyvinyl alcohol aqueous solution with a mass concentration of 5% are added, and the mixture is poured into a rotation-revolution mixer and mixed at 2100rpm for 2 minutes. Repeat three times to obtain a uniformly mixed porous ceramic slurry.
[0030] 2) Injection Molding: Add 1 part of ammonium persulfate to the uniformly mixed porous ceramic slurry obtained in step 1), pour into a mold, and place in a water bath at 60° C. for 30 minutes to wait for molding.
[0031] 3) Material post-processing The formed ceramic processing material prepared in step 2) is dried in a constant temperature and humidity chamber at 25°C and 80% relative humidity for 12 hours, at 40°C and 60% relative humidity for 12 hours, and at 80°C and 20% relative humidity for 24 hours; degreasing and sintering are performed in an atmospheric atmosphere sintering furnace with a maximum sintering temperature of 1350°C and a holding time of 2 hours to obtain a porous ceramic material.
[0032] 4) Performance testing The density, flexural strength and apparent porosity of the porous ceramic material prepared in step 3) are tested, and the color of the prepared porous ceramic material is recorded, wherein the porosity is tested in accordance with GB / T25995-2010; the flexural strength is tested in accordance with GBT_6569-2006.
[0033] Comparative Example 2 The difference between this comparative example and Example 1 is that in this comparative example, 4 parts of iron oxide powder and 1 part of chromium trioxide are added in step 1), that is, the ratio of the colorant is changed, and the rest of the process is the same as that in Example 1. The specific steps are as follows: 1) Preparation of slurry By weight, 42 parts of particle size D 10 =0.3μm, D 50 =0.5μm, D 90 = 3μm alumina powder, 11 parts particle size D 10 =0.8μm, D 50 =1μm, D 90=5μm silicon dioxide powder, 4 parts of iron oxide powder, 1 part of chromium trioxide, 1.5 parts of cobalt trioxide, 0.5 parts of nickelous oxide are mixed with 24 parts of deionized water, and then 1.5 parts of polyacrylic acid, 7 parts of N-hydroxymethyl acrylamide, and 0.5 parts of N, N'-methylenebisacrylamide are added, and ball milling is carried out for 60 minutes until the bulk material is uniform, and then 38 parts of coarse white corundum powder, 30 parts of polymethyl methacrylate microspheres, and 36 parts of polyvinyl alcohol aqueous solution with a mass concentration of 5% are added, and the mixture is poured into a rotation-revolution mixer and mixed at 2100rpm for 2 minutes. Repeat three times to obtain a uniformly mixed porous ceramic slurry.
[0034] 2) Injection Molding: Add 1 part of ammonium persulfate to the uniformly mixed porous ceramic slurry obtained in step 1), pour into a mold, and place in a water bath at 60° C. for 30 minutes to wait for molding.
[0035] 3) Material post-processing The formed ceramic processing material prepared in step 2) is dried in a constant temperature and humidity chamber at 25°C and 80% relative humidity for 12 hours, at 40°C and 60% relative humidity for 12 hours, and at 80°C and 20% relative humidity for 24 hours; degreasing and sintering are performed in an atmospheric atmosphere sintering furnace with a maximum sintering temperature of 1350°C and a holding time of 2 hours to obtain a porous ceramic material.
[0036] 4) Performance testing The density, flexural strength and apparent porosity of the porous ceramic material prepared in step 3) are tested, and the color of the prepared porous ceramic material is recorded, wherein the porosity is tested in accordance with GB / T25995-2010; the flexural strength is tested in accordance with GBT_6569-2006.
[0037] Table 1 Effect of colorant ratio on the properties of the final porous ceramics It can be concluded from the data in Table 1 that when the colorant ratio is changed, that is, the content of iron oxide is too high or the content of cobalt trioxide is too high, the color of the porous ceramics finally obtained will change, but other properties of the porous ceramics such as apparent porosity, density and bending strength will not be greatly affected. It is speculated that the main properties of the porous ceramics in this patent are determined by the main material white corundum and pores. The difference between Comparative Example 1 and Comparative Example 2 is that one adds more chromium trioxide and the other adds more iron oxide. Comparing these two materials, iron oxide is not only an excellent colorant, but also an efficient Sintering aids make the sintering degree of alumina deeper, so the bending strength is slightly increased and the apparent porosity is slightly reduced, but the overall impact is small. However, the impact on color is large and cannot meet the requirements of this material. Chromium trioxide is more used as a colorant and has no obvious sintering effect. Therefore, after adding more chromium trioxide, not only the color changes, but its apparent porosity, density and bending strength all decrease, and the closed porosity increases. In summary, excessive addition of a certain colorant will not have a beneficial effect on the target product, and the most suitable ratio needs to be found.
[0038] Comparative Example 3 The difference between this comparative example and Example 1 is that in this comparative example, 15 parts of polymethyl methacrylate microspheres as a pore-forming agent are added in step 1), that is, the ratio of the pore-forming agent is changed, and the rest of the process is the same as that in Example 1, and the specific steps are as follows: 1) Preparation of slurry By weight, 42 parts of particle size D 10 =0.3μm, D 50 =0.5μm, D 90 = 3μm alumina powder, 11 parts particle size D 10 =0.8μm, D 50 =1μm, D 90 =5μm silicon dioxide powder, 3 parts of iron oxide powder, 2 parts of chromium trioxide, 1.5 parts of cobalt trioxide, 0.5 parts of nickelous oxide are mixed with 24 parts of deionized water, and then 1.5 parts of polyacrylic acid, 7 parts of N-hydroxymethyl acrylamide, and 0.5 parts of N, N'-methylenebisacrylamide are added, and ball milling is carried out for 60 minutes until the bulk material is uniform, and then 38 parts of coarse white corundum powder, 15 parts of polymethyl methacrylate microspheres, and 36 parts of polyvinyl alcohol aqueous solution with a mass concentration of 5% are added, and the mixture is poured into a rotation-revolution mixer and mixed at 2100rpm for 2 minutes. Repeat three times to obtain a uniformly mixed porous ceramic slurry.
[0039] 2) Injection molding One portion of ammonium persulfate was added to the uniformly mixed porous ceramic slurry obtained in step 1), and the mixture was poured into a mold. The mold was placed in a water bath at 60° C. for 30 minutes to wait for molding.
[0040] 3) Material post-processing The formed ceramic processing material prepared in step 2) is dried in a constant temperature and humidity chamber at 25°C and 80% relative humidity for 12 hours, at 40°C and 60% relative humidity for 12 hours, and at 80°C and 20% relative humidity for 24 hours; degreasing and sintering are performed in an atmospheric atmosphere sintering furnace with a maximum sintering temperature of 1350°C and a holding time of 2 hours to obtain a porous ceramic material.
[0041] 4) Performance testing The density, flexural strength and apparent porosity of the porous ceramic material prepared in step 3) are tested, and the color of the prepared porous ceramic material is recorded, wherein the porosity is tested in accordance with GB / T25995-2010; the flexural strength is tested in accordance with GBT_6569-2006.
[0042] Comparative Example 4 The difference between this comparative example and Example 1 is that in this comparative example, 40 parts of polymethyl methacrylate microspheres as a pore-forming agent are added in step 1), that is, the ratio of the pore-forming agent is changed, and the rest of the process is the same as that in Example 1, and the specific steps are as follows: 1) Preparation of slurry By weight, 42 parts of particle size D 10 =0.3μm, D 50 =0.5μm, D 90 = 3μm alumina powder, 11 parts particle size D 10 =0.8μm, D 50 =1μm, D 90 =5μm silicon dioxide powder, 3 parts of iron oxide powder, 2 parts of chromium trioxide, 1.5 parts of cobalt trioxide, 0.5 parts of nickelous oxide are mixed with 24 parts of deionized water, and then 1.5 parts of polyacrylic acid, 7 parts of N-hydroxymethyl acrylamide, and 0.5 parts of N, N'-methylenebisacrylamide are added, and ball milling is carried out for 60 minutes until the bulk material is uniform, and then 38 parts of coarse white corundum powder, 40 parts of polymethyl methacrylate microspheres, and 36 parts of polyvinyl alcohol aqueous solution with a mass concentration of 5% are added, and the mixture is poured into a rotation-revolution mixer and mixed at 2100rpm for 2 minutes. Repeat three times to obtain a uniformly mixed porous ceramic slurry.
[0043] 2) Injection Molding: Add 1 part of ammonium persulfate to the uniformly mixed porous ceramic slurry obtained in step 1), pour into a mold, and place in a water bath at 60° C. for 30 minutes to wait for molding.
[0044] 3) Material post-processing The formed ceramic processing material prepared in step 2) is dried in a constant temperature and humidity chamber at 25°C and 80% relative humidity for 12 hours, at 40°C and 60% relative humidity for 12 hours, and at 80°C and 20% relative humidity for 24 hours; degreasing and sintering are performed in an atmospheric atmosphere sintering furnace with a maximum sintering temperature of 1350°C and a holding time of 2 hours to obtain a porous ceramic material.
[0045] 4) Performance testing The density, flexural strength and apparent porosity of the porous ceramic material prepared in step 3) are tested, and the color of the prepared porous ceramic material is recorded, wherein the porosity is tested in accordance with GB / T25995-2010; the flexural strength is tested in accordance with GBT_6569-2006.
[0046] Table 2 Effect of the ratio of pore-forming agents on the properties of porous ceramic materials From the data in Table 2, it can be concluded that when the amount of pore-forming agent added is too little, the apparent porosity of the porous ceramic material produced will decrease, and the vacuum suction cup produced will increase the error rate of the processed workpiece due to the decrease in the number of pores; while when the amount of pore-forming agent added is too much, although the apparent porosity of the porous ceramic material will increase, it will also cause the density of the porous material to decrease and the bending strength to decrease, and the overall performance will be greatly reduced. In summary, the balance of Example 1 is the best option, because it has a higher apparent porosity and mechanical properties at the same time, which prevents the risk of the vacuum suction cup from breaking during the product processing process. Comparative Example 5 The difference between this comparative example and Example 1 is that in this comparative example, in step 1), coarse white corundum powder is not added, and the rest of the process is the same as that in Example 1, and the specific steps are as follows: 1) Preparation of slurry By weight, 42 parts of particle size D 10 =0.3μm, D 50 =0.5μm, D 90 = 3μm alumina powder, 11 parts particle size D 10 =0.8μm, D 50 =1μm, D 90=5μm silicon dioxide powder, 3 parts of iron oxide powder, 2 parts of chromium trioxide, 1.5 parts of cobalt trioxide, 0.5 parts of nickelous oxide are mixed with 24 parts of deionized water, and then 1.5 parts of polyacrylic acid, 7 parts of N-hydroxymethyl acrylamide, and 0.5 parts of N, N'-methylenebisacrylamide are added, and ball milling is carried out for 60 minutes until the bulk material is uniform, and then 30 parts of polymethyl methacrylate microspheres and 36 parts of polyvinyl alcohol aqueous solution with a mass concentration of 5% are added, and the mixture is poured into a rotation-revolution mixer and mixed at 2100rpm for 2 minutes. Repeat three times to obtain a uniformly mixed porous ceramic slurry.
[0047] 2) Injection Molding: Add 1 part of ammonium persulfate to the uniformly mixed porous ceramic slurry obtained in step 1), pour into a mold, and place in a water bath at 60° C. for 30 minutes to wait for molding.
[0048] 3) Material post-processing The formed ceramic processing material prepared in step 2) is dried in a constant temperature and humidity chamber at 25°C and 80% relative humidity for 12 hours, at 40°C and 60% relative humidity for 12 hours, and at 80°C and 20% relative humidity for 24 hours; degreasing and sintering are performed in an atmospheric atmosphere sintering furnace with a maximum sintering temperature of 1350°C and a holding time of 2 hours to obtain a ceramic material.
[0049] 4) Performance testing The density, flexural strength and apparent porosity of the ceramic material prepared in step 3) are tested, and the color of the porous ceramic material is recorded, wherein the porosity is tested in accordance with GB / T25995-2010; the flexural strength is tested in accordance with GBT_6569-2006.
[0050] Table 3 Effect of coarse white corundum powder on porous ceramic materials It can be concluded from the data in Table 3 that if no coarse white corundum powder is added to the slurry at all, the ceramic material finally generated can basically not generate open pores. A large number of circular closed pores can be observed under electron microscope observation. It is speculated that when all white corundum particles are replaced with alumina powder, the fine alumina powder and silica liquid phase will completely wrap PMMA to form closed pores that do not interfere with each other. In this patent, the white corundum used is an irregular oblong block, and the alumina powder used is spherical. Because of the shape and particle size of alumina, it has a higher packing density than white corundum. With the cooperation of sintering aids, alumina powder forms an obvious sintering neck at 1450°C, the grains begin to grow, and the pores between the grain boundaries are gradually filled, resulting in the disappearance of a large number of pores. When white corundum is added, large particles of white corundum have a higher melting point than conventional alumina powder. At the current sintering temperature, its size and morphology are not easy to change, avoiding the generation of sintering necks and no obvious grain growth process, and its irregular morphology has a lower packing density. When white corundum is added, the liquid phase formed by a small amount of alumina powder and a low ratio of silicon dioxide only serves as a connection and cannot completely wrap the white corundum skeleton.
[0051] Example 2 1) Preparation of slurry By weight, 42 parts of particle size D 10 =0.3μm, D 50 =0.5μm, D 90 = 3μm alumina powder, 11 parts particle size D 10 =0.8μm, D 50 =1μm, D 90 =5μm silicon dioxide powder, 3 parts of iron oxide powder, 2 parts of chromium trioxide, 1.5 parts of cobalt trioxide, 0.5 parts of nickelous oxide are mixed with 60 parts of deionized water, and then 1.5 parts of polyacrylic acid, 7 parts of N-hydroxymethyl acrylamide, and 0.5 parts of N, N'-methylenebisacrylamide are added, and ball milling is carried out for 60 minutes until the bulk material is uniform, and then 38 parts of coarse white corundum powder, 30 parts of spherical graphite powder, and 36 parts of polyvinyl alcohol aqueous solution with a mass concentration of 5% are added, and the mixture is poured into a rotation-revolution mixer and mixed at 2100rpm for 2 minutes. Repeat three times to obtain a uniformly mixed porous ceramic slurry.
[0052] 2) Injection Molding: Add 1 part of ammonium persulfate to the uniformly mixed porous ceramic slurry obtained in step 1), pour into a mold, and place in a water bath at 60° C. for 30 minutes to wait for molding.
[0053] 3) Material post-processing The formed ceramic processing material prepared in step 2) is dried in a constant temperature and humidity chamber at 25°C and 80% relative humidity for 12 hours, at 40°C and 60% relative humidity for 12 hours, and at 80°C and 20% relative humidity for 24 hours; degreasing and sintering are performed in an atmospheric atmosphere sintering furnace with a maximum sintering temperature of 1350°C and a holding time of 2 hours to obtain a porous ceramic material.
[0054] 4) Performance testing The density, flexural strength and apparent porosity of the porous ceramic material prepared in step 3) are tested, and the color of the prepared porous ceramic material is recorded, wherein the porosity is tested in accordance with GB / T25995-2010; the flexural strength is tested in accordance with GBT_6569-2006.
[0055] Example 3 1) Preparation of slurry By weight, 42 parts of particle size D 10 =0.3μm, D 50 =0.5μm, D 90 = 3μm alumina powder, 11 parts particle size D 10 =0.8μm, D 50 =1μm, D 90 =5μm silicon dioxide powder, 3 parts of iron oxide powder, 2 parts of chromium trioxide, 1.5 parts of cobalt trioxide, 0.5 parts of nickelous oxide and 24 parts of deionized water are mixed, and then 1.5 parts of polyacrylic acid, 7 parts of N-hydroxymethyl acrylamide and 0.5 parts of N, N'-methylenebisacrylamide are added, and ball milling is carried out for 60 minutes until the bulk material is uniform, and then 38 parts of coarse white corundum powder, 30 parts of industrial starch and 36 parts of polyethylene oxide aqueous solution with a mass concentration of 5% are added, and the mixture is poured into a rotation-revolution mixer and mixed at 2100rpm for 2 minutes, and repeated three times to obtain a uniformly mixed porous ceramic slurry.
[0056] 2) Injection Molding: Add 1 part of ammonium persulfate to the uniformly mixed porous ceramic slurry obtained in step 1), pour into a mold, and place in a water bath at 60° C. for 35 minutes to wait for molding.
[0057] 3) Material post-processing The formed ceramic processing material prepared in step 2) is dried in a constant temperature and humidity chamber at 25°C and 80% relative humidity for 12 hours, at 40°C and 60% relative humidity for 12 hours, and at 80°C and 20% relative humidity for 24 hours; degreasing and sintering are performed in an atmospheric atmosphere sintering furnace with a maximum sintering temperature of 1350°C and a holding time of 2 hours to obtain a porous ceramic material.
[0058] 4) Performance testing The density, flexural strength and apparent porosity of the porous ceramic material prepared in step 3) are tested, and the color of the prepared porous ceramic material is recorded, wherein the porosity is tested in accordance with GB / T25995-2010; the flexural strength is tested in accordance with GBT_6569-2006.
[0059] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0060] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a black alumina porous ceramic material for a vacuum chuck, characterized in that: The following steps are involved: 1) After mixing 4-5 parts of aluminum oxide powder, 10-11 parts of silicon dioxide powder, 7-8 parts of colorant and 20-25 parts of water by weight, 0.5-1 parts of polyacrylic acid, 6-8 parts of N-hydroxymethyl acrylamide and N,N'-methylenebisacrylamide are added, and ball milling is performed for 30-60 minutes, wherein the colorant is iron oxide powder, chromium trioxide, cobalt trioxide and nickelous oxide; 2) Add 35-40 parts of white corundum coarse powder, 30-35 parts of pore-forming agent and 35-38 parts of suspending agent and centrifuge for 2-3 minutes, repeat 3-5 times; 3) Add 1-1.5 parts of ammonium persulfate and stir evenly, pour into a mold, and let stand at 60-65°C for 30-45 minutes; 4) After demoulding and drying, degreasing and sintering are performed to obtain the material.
2. The method for preparing a black alumina porous ceramic material for a vacuum chuck according to claim 1, characterized in that: In step 1), the colorant is iron oxide powder, chromium oxide, cobalt oxide and nickelous oxide in a weight ratio of (2.8-3.2): (1.8-2.2): (1.3-1.5): (0.4-0.6).
3. The method for preparing a black alumina porous ceramic material for a vacuum chuck according to claim 1, characterized in that: In step 1), the particle size of the alumina powder is: D 10 =0.3~0.35μm; D 50 =0.5~0.55μm; D 90 =3~3.1μm.
4. The method for preparing a black alumina porous ceramic material for a vacuum chuck according to claim 1 or 3, characterized in that: In step 1), the particle size of the silicon dioxide powder is: D 10 =0.8~0.85μm; D 50 =1~1.05μm; D 90 =5~5.2μm.
5. The method for preparing a black alumina porous material for a vacuum chuck according to claim 1, characterized in that: In step 2), the white corundum coarse powder is fused white corundum, and the particle size is: D 10 =10~11μm; D 50 =15~16μm; D 90 =25~26μm.
6. The method for preparing a black alumina porous ceramic material for a vacuum chuck according to claim 1 or 5, characterized in that: In step 2), the pore-forming agent is one or more of polymethyl methacrylate, spherical graphite, and industrial starch, and the particle size is: D 10 =30~40μm; D 50 =45~55μm; D 90 =55~70μm.
7. The method for preparing a black alumina porous ceramic material for a vacuum chuck according to claim 1, wherein: In step 2), the suspending agent is one or more of polyvinyl alcohol and polyethylene oxide aqueous solutions with a concentration of 5-6 wt%.
8. The method for preparing a black alumina porous ceramic material for a vacuum chuck according to claim 1, characterized in that: In step 4), the drying process is: drying at 40-45° C. and relative humidity of 80-85% for 24-30 hours, drying at 60-65° C. and relative humidity of 40-45% for 24-30 hours, and finally drying at 80-85° C. and relative humidity of 20-25% for 24-30 hours.
9. The method for preparing a black alumina porous ceramic material for a vacuum chuck according to claim 1, characterized in that: Step 4), the temperature of debinding and sintering is 1400-1450°C, and the time of debinding and sintering is 2-3h.
10. A black alumina porous ceramic material for a vacuum chuck prepared by the method for preparing a black alumina porous ceramic material for a vacuum chuck according to any one of claims 1 to 9.
Citation Information
Patent Citations
Black alumina-based ceramic substrate and preparation method thereof
CN117585990A
Alumina-based opaque ceramic
CN102947245A
Low temperature sintered alumina black ceramic, and preparation method thereof
CN110330315A
Preparation method of zirconia ceramic mobile phone backboard with black gold sand effect
CN112745119A
Preparation method of alumina porous ceramic
CN114105615A